2014
DOI: 10.18632/oncotarget.2831
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors beyond prostate cancer: an old marker as a new target

Abstract: Androgen receptors (ARs) play a critical role in the development of prostate cancer. Targeting ARs results in important salutary effects in this malignancy. Despite mounting evidence that ARs also participate in the pathogenesis and/or progression of diverse tumors, exploring the impact of hormonal manipulation of these receptors has not been widely pursued beyond prostate cancer. This review describes patterns of AR expression in a spectrum of cancers, and the potential to exploit this knowledge in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…AR binds to its native ligand, 5α-dihydrotestosterone (DHT), with strong affinity in the nucleus. AR dimers bind to androgen response elements (AREs) in the promoter region of target genes [ 4 ]. AR has biological actions in both health and disease and participates in both normal physiological processes and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…AR binds to its native ligand, 5α-dihydrotestosterone (DHT), with strong affinity in the nucleus. AR dimers bind to androgen response elements (AREs) in the promoter region of target genes [ 4 ]. AR has biological actions in both health and disease and participates in both normal physiological processes and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these more conventional approaches, there is growing interest in androgen antagonism in gynecologic cancer treatment. Although androgen antagonism was historically limited to prostate cancer treatment, the development of more effective second-generation drugs has expanded the potential reach of this approach to other tumor types 13. Recent studies in endometrial carcinoma have shown some benefit to androgen antagonisms in androgen receptor-positive endometrial carcinoma primaries and metastases,11 12 and androgen antagonism has also been suggested as a therapeutic option for serous ovarian carcinomas expressing androgen receptor 21 22.…”
Section: Discussionmentioning
confidence: 99%
“…Despite mounting evidence that AR participates in the tumorigenesis and/or progression of diverse tumors, the mechanisms of how AR signaling contributes to carcinogenesis are poorly understood [ 10 ]. Most prostate cancer cells express androgen receptor and androgen signaling plays a major role in the proliferation of prostate cancer cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barboro et al reported that a high percentage of AR-positive cells is associated with a good prognosis in prostate cancer patients [ 8 ], however there are conflicting results and the prognostic value of AR expression in prostate cancer and its clinical relevance is still debated [ 9 ]. Besides prostate cancer, AR expression has been described in a wide range of solid tumors including sarcomas, melanomas and carcinomas [ 10 ]. High AR expression is associated with lower recurrence rates and better prognosis in bladder cancer [ 11 ] and improved survival in serous carcinoma of the ovary [ 12 ], advanced squamous cell carcinoma of the head and neck [ 13 ], and breast cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%